the Teams Games Tournament (TGT) Type Cooperative Learning Model to Improve History Learning Outcomes for Class XII IPS - Putra*, Faisal Akbar Dwi; Sumantri, Pulung; Nasution, Imsar Muda (Universitas Syiah Kuala, 2024)
The aim of this research is to use Classroom Action Research (PTK) to analyze the application of the Teams Game Tournament (TGT) type cooperative learning model to student learning outcomes. The research consisted of two cycles with a research sample of all class XII IPS 1 students at SMA Negeri 1 Medan, totaling 35 students. This research design is a quantitative approach using pre-test and post-test question instruments to determine the success of improving student learning outcomes in implementing the Teams Game Tournament (TGT) learning model. Based on data analysis of student learning outcomes, student learning outcomes experienced an increase in learning mastery as shown in the pretest (65.7%), Cycle I (88.5%), and Cycle II (97.1%). The application of the team game tournament (TGT) type cooperative learning model can improve the history learning outcomes of class XII IPS 1 students at SMA Negeri 1 Medan.